Pengaruh Inovasi Produk dan Harga Terhadap Keputusan Pembelian Produk Miniso pada Mahasiswa D-IV Manajemen Pemasaran Politeknik Negeri Malang - Deky Kurnianto; Tri Yulistyawati Evelina (STIKes Ibnu Sina Ajibarang, 2025)
This research is quantitative research with variable X, namely Product Innovation and Price, against variable Y, namely Purchasing Decisions. This research uses observation and questionnaire data collection techniques, and with techniques non probabability sampling 70 respondents were obtained from D-IV Marketing Management students. This research uses multiple linear regression analysis and coefficient of determination analysis. The results of the analysis of hypothesis test were partial, product innovation has a positive and significant effect on the purchasing decision, then the price partially has no positive and significant effect on the purchasing decision. The results of the simultaneous hypothesis testing the variables of Product Innovation and Price have a positive and significant effect on the purchasing decision. The results of this research, simultaneously the variables of Product Innovation and Price have a positive and significant effect on the purchasing decision of Miniso Products on D-IV Marketing Management Students at Polytechnic State of Malang.